Kreatif Menanam, Asyik Mendaur Ulang di SD Palalangan 2, Kecamatan Cermee, Kabupaten Bondowoso - Shinta Yama Diwipa; Adella Mutia Devi; Ahsan Sutio Ivandi; Devan Eka Iswahyudi; Rio Raditiya Ardiyansah; Azizah Nur Laili; Moh Rois Fawwaz; Oria Alit Farisi; Dwi Erwin Kusbianto; Agung Nugroho Puspito (Jurnal Pengabdian Nasional (JPN) Indonesia, 2026)
Education serves as a vital factor in society, forming the foundation for shaping children's character and personality. A social project was implemented to provide knowledge to elementary school children at SD Palalangan 2, Cermee District, Bondowoso Regency, involving all students from grades 1 to 6. The program included: pre-test, introduction to plant parts, instruction on planting kale using soil media, knowledge on reusing containers, kale plant maintenance, educational games about plant parts, and post-test. The social project entitled "Creative Planting, Fun Recycling" was successfully implemented. Pre-test results showed that only a small number of students understood how to plant, care for plants, and recognize plant parts and their functions. Post-test results demonstrated that most students gained understanding of planting techniques, plant care, and plant anatomy with their functions. The program successfully enhanced students' understanding of cultivation techniques, plant maintenance, and plant anatomy at SD Palalangan 2